Creación de un plan de negocio para una empresa dedicada a realizar acabados de construcción y mantenimiento preventivo - Arias Iguago, Mauricio Alejandro (2023)
The objective of the present investigation is to design a business plan for the company "SETEMA" which seeks to collaborate with the security in the homes of a part of the Metropolitan District of Quito, providing preventive maintenance services in aluminum and glass structures, to which a theoretical foundation was made, organizing information, to have a technical support with which to develop the work. Subsequently, a market study was carried out where a target population of 385 households was defined, which expressed their preference for safety, choosing high-quality accessories and qualified personnel. This served as the basis for defining the mission and vision that the company will follow. Next, the processes for the delivery of the service were designated. Finishing with a financial study and a forecast of sales and expenses that the company will have. Once the analyzes were carried out, a Net Present Value of $25,056.65 was obtained, ratifying the viability of the project as it is greater than zero, in addition, the value of the Internal Rate of Return was obtained with a value of 32%, this being greater than the Minimum Acceptable Rate of Yield of 30.4%, which indicates that it is more profitable to invest in the project than in the financial system.